2003
DOI: 10.1046/j.1365-3059.2003.00873.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Pochonia chlamydosporia in a double‐cropping system of lettuce and tomato in plastic houses infested with Meloidogyne javanica

Abstract: The effect of Pochonia chlamydosporia , a facultative fungal parasite of nematode eggs, alone or in combination with oxamyl was evaluated in a double-cropping system of lettuce and tomato in unheated plastic houses infested with Meloidogyne javanica at two sites for two consecutive growing seasons. An additional treatment of methyl bromide fumigation was included to compare crop yield in nematode-free vs. nematode-infested soil. Final population densities, reproductive rate, root gall rating, and egg productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(31 citation statements)
references
References 12 publications
2
27
0
2
Order By: Relevance
“…Lettuce, Lactuca sativa type Maravilla cv. Arena, rotated with tomato from October to February, did not support nematode reproduction (Verdejo-Lucas et al, 2003).…”
Section: Plastic-house Experimentsmentioning
confidence: 84%
See 1 more Smart Citation
“…Lettuce, Lactuca sativa type Maravilla cv. Arena, rotated with tomato from October to February, did not support nematode reproduction (Verdejo-Lucas et al, 2003).…”
Section: Plastic-house Experimentsmentioning
confidence: 84%
“…Observation of these premises resulted in undetectable root-knot nematode levels in plastic-houses for at least 2 years (Verdejo- Lucas et al, 2003), although the nematode can be found in methyl bromide fumigated soils after cultivation of a single crop . Since agriculture is an economic activity, any control method can only be justified if the increased value of the crop is equal or greater than the cost of the control method.…”
Section: Discussionmentioning
confidence: 99%
“…In biological control experiments of root-knot nematodes in plastic tunnel houses, one of the treatments involved the inoculation of soil with P. chlamydosporia isolate IACRVc-10 (equal to our isolate 144). The extent of biocontrol by the fungus was low, and furthermore, the antagonist was reisolated at very low rates in the rhizospheres of the test plants (Verdejo-Lucas et al 2003). In the current experiments, isolate 144 was one of the most sensitive fungi in both soils.…”
Section: Discussionmentioning
confidence: 99%
“…Cette diversité pourrait aussi affecter négativement l'efficacité des agents de lutte biologique du fait de leur sélectivité par rapport aux espèces de nématodes. Verdejo-Lucas et al (2003) ont à cet effet suggéré que la gestion durable des nématodes à galles ne pourrait être effective que grâce à une combinaison de méthodes de lutte. Des études antérieures ont démontré l'effectivité de la lutte contre les nématodes à galles lorsque les dérivés de neem sont associés à des agents biologiques comme Paecilomyces lilacinus, Pasteuria penetrans Trichoderma harzianum ou champignons mycorhiziens arbusculaires (Glomus mosseae) (Coyne et al, 2009).…”
Section: Discussionunclassified